Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep19304
|View full text |Cite
|
Sign up to set email alerts
|

Efficient extravasation of tumor-repopulating cells depends on cell deformability

Abstract: Cancer metastasis is the most deadly stage in cancer progression. Despite significant efforts over the past decades, it remains elusive why only a very small fraction of cancer cells is able to generate micrometastasis and metastatic colonization. Recently we have shown that tumor-repopulating cells (TRCs), a highly tumorigenic subpopulation of mouse melanoma cells, can be selected by being cultured and grown in 3D soft fibrin gels. Here we show that when injected into the yolk of a 2 day-post-fertilization (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…We recently showed that blood flow tunes CTC arrest by a process which is encoded into a tug-of-war between blood flowdriven shear stress and the limited adhesive power of CTCs (Figure 1, Follain et al, 2018). CTC adhesion to the endothelium, preceding their exit from the bloodstream, has been extensively studied either in vitro (Aigner et al, 1998;Chen et al, 2016a;Giavazzi et al, 1993;Laferrière et al, 2001Laferrière et al, , 2004Reymond et al, 2012;Tremblay et al, 2008) or in vivo (Hiratsuka et al, 2011;Köhler et al, 2010;Stoletov et al, 2010) for the past 30 years. These studies identified adhesion receptors used by CTCs to arrest within the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that blood flow tunes CTC arrest by a process which is encoded into a tug-of-war between blood flowdriven shear stress and the limited adhesive power of CTCs (Figure 1, Follain et al, 2018). CTC adhesion to the endothelium, preceding their exit from the bloodstream, has been extensively studied either in vitro (Aigner et al, 1998;Chen et al, 2016a;Giavazzi et al, 1993;Laferrière et al, 2001Laferrière et al, , 2004Reymond et al, 2012;Tremblay et al, 2008) or in vivo (Hiratsuka et al, 2011;Köhler et al, 2010;Stoletov et al, 2010) for the past 30 years. These studies identified adhesion receptors used by CTCs to arrest within the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the α subunit (ITGA) mediating stable adhesion of CTCs, and thereby identify its ligand, we depleted ITGA4, 3 and 5 ( Figure S2D,S3A). When associated to ITGB1, they respectively mediate binding to luminal VCAM (Klemke et al, 2007), to laminin (Chen et al, 2016a) and to fibronectin (Huveneers et al, 2008) of the basal ECM. We discarded the participation of ITGA4 and observed that ITGA3 was not required for the formation of stable cell adhesion to the endothelial layer ( Figure S3B-C).…”
Section: Cd44 Itgb3 and Itgb1 Favor Arrest Of Ctcs Yet Only Itgb1 Imentioning
confidence: 99%
“…These soft melanoma TRCs also extravasate (move out of the blood vessels) to secondary sites more efficiently (Fig. 2) than those stiff differentiated melanoma cells [93]. These findings suggest a common thread in metastatic colonization of malignant tumors: a few tumorigenic TRCs are able to metastasize and grow at the secondary sites of soft matrices because these cells exert low forces, are soft and undifferentiated.…”
Section: Mechanobiology In Mechanobiomedicinementioning
confidence: 99%
“…The undifferentiated soft TRCs arrest at the tail and squeezed out of the small blood vessel (green color) more efficiently than the differentiated stiff control melanoma cells. The efficient extravasation of the soft TRCs and the ensuing micrometastasis formation and metastatic colonization is inhibited by differentiating the TRCs with retinoic acid, stiffening F-actin with a polymerizing drug, or promoting F-actin via overexpressing small GTPase Cdc42 (from [93]).…”
Section: Figurementioning
confidence: 99%
“…In addition to the extrinsic biophysical signals that may regulate CSC behavior, recent reports have also shown that CSCs themselves exhibit changes in their mechanical properties when compared to the bulk tumor population [3234]. Several reports have indicated an increase in mechanical deformability as an important identifier of CSC populations [32,33].…”
Section: Introductionmentioning
confidence: 99%